Treatment rates for sea lice of Scottish inshore marine salmon farms depend on local (sea loch) farmed salmon biomass and oceanography - AG Murray (Inter-Research, 2014)
Sea lice are the most damaging parasite of marine-farmed salmon. Lice are controlled largely by using medicines. Discharge consents limit the allowed medicine use and hence biomass of salmon that can be farmed. The local environment may be expected to play a role in determining the frequency of application of these medicines on specific salmon farm sites. To assess this, we used data collected by the Scottish Environment Protection Agency on lice treatments and fish biomasses from 2005 to 2012 for salmon farm sites located within sea lochs (offshore sites are not included), together with local hydrographic data. There was relatively little variation in treatment rates between different sites within a loch, so a loch (or larger unit) is the appropriate area for analysis of factors influencing these treatment rates. Treatment rates tended to increase with the loch’s total biomass of farmed salmon. Dependence of treatment rate on loch flushing time was highly significant in all regions; however, dependence was positive in the Northern and Western Isles but negative in mainland Scotland. A possible explanation is flushing of lice away from island sea lochs but into mainland sea lochs, in line with prevailing currents. Regional variation in dependence suggests that oceanographic processes at larger spatial scales play a significant role in determining lice dynamics.